2015
DOI: 10.1017/s2045796015000918
|View full text |Cite
|
Sign up to set email alerts
|

Staging cognitive impairment and incidence of dementia

Abstract: The documented gradient of increased risk of dementia associated with the severity level of cognitive impairment supports the validity of the simple staging model based on the MMSE assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
(145 reference statements)
0
3
0
Order By: Relevance
“…Within our sample, three clear and conceptually cohesive groups were identified based on the collective score profiles from the above measures, reflective of mild, moderate, and severe levels of dementia (Table 1). Specifically, these groups emerged based primarily on a synthesis of the cognitive and functional abilities retained in each of the LACLS-5 ratings, the MMSE score, the DRS-2 subscales, ADL and IADL scores, degree of behavioral symptoms, and information in the literature that helped align participants' scores and abilities with mild, moderate, and severe stages of cognitive impairment (Alzheimer's Association, n.d.; Perneczky et al, 2006;Santabárbara et al, 2015).…”
Section: Dementia Disease Stagementioning
confidence: 99%
“…Within our sample, three clear and conceptually cohesive groups were identified based on the collective score profiles from the above measures, reflective of mild, moderate, and severe levels of dementia (Table 1). Specifically, these groups emerged based primarily on a synthesis of the cognitive and functional abilities retained in each of the LACLS-5 ratings, the MMSE score, the DRS-2 subscales, ADL and IADL scores, degree of behavioral symptoms, and information in the literature that helped align participants' scores and abilities with mild, moderate, and severe stages of cognitive impairment (Alzheimer's Association, n.d.; Perneczky et al, 2006;Santabárbara et al, 2015).…”
Section: Dementia Disease Stagementioning
confidence: 99%
“…Studies have demonstrated that physical frailty and mild cognitive impairment are the early stages of disability and dementia (Fried et al., 2001; Makizako, Shimada, Doi, Tsutsumimoto, & Suzuki, 2015; Petersen et al., 2018; Santabarbara et al., 2016). Physical frailty refers to a biologic syndrome of decreased reserve and resistance to stressors resulting from cumulative declines across multiple physiologic systems, and can be quantified by the presence of at least three of the following five physical components: poor nutrition, slow walking speed, limited grip strength, low physical activity and decreased endurance (Fried et al., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach that has been used within the staging of dementia is based on severity of cognitive impairment through use of established tools that measure cognition, such as the MMSE [32]. For example, previous work by Santabárbara et al (2016) [33] found an increased risk of dementia associated with the severity level of cognitive impairment, as measured by the MMSE.…”
Section: Recent Work On Other Staging Toolsmentioning
confidence: 99%